Food talk: A window into inequality among university students - Dominguez-Whitehead, Yasmine; Dominguez-Whitehead, Kevin A. (My University, 2014)
Although initially related to the country’s colonial and apartheid history, material inequality in South Africa has deepened, with recent research suggesting that South Africa now has the highest levels of inequality in the world. In this paper, we examine the interactional reproduction of inequality by paying particular attention to the discursive and interactional practices employed in students’ talk about food. Specifically, we examine food-related troubles talk and food-related jokes and humor, showing how students who described food-related troubles produced these troubles as shared and systemic, while students who produced food-related jokes displayed that they take for granted the material resources needed to have a range of food consumption choices available to them, while treating food consumption as a matter of individual choice. These orientations were collaboratively produced through a range of interactionally organized practices, including patterns of alignment and dis-alignment, pronoun use, laughter, and aspects of the formulation of utterances. While our analysis primarily focuses on these discursive and interactional practices, we also consider how discursive practices can be linked to the material conditions of participants’ lives outside of the analyzed interactions.
Keywords: Food acquisition – Tertiary students – South Africa; Poverty – Tertiary students – South Africa; South African universities – Food on campus; Student inequality – South African higher education; Troubles talk – Tertiary students – South Africa; Jokes and humor -- university students -- South Africa